A construção do ator “Benjamin” em O Palhaço de Selton Mello: uma abordagem semiótica - Sousa, Tatiana Barbosa de (2015)
Based on the French Semiotic Theory, this research analyses the movie O Palhaço, directed and starred by Selton Mello. The movie shows Benjamin’s inner conflicts that start in a decadent circus during the 1970’s. The insatisfaction state of soul of the actor Benjamin, a clown that smiles on the outside and cries on the inside, starts to affect everybody who is around him. So, when his father Valdemar questions him about what his role in the world really is, the actor decides to abandon the circus so that he could find his true identity. Our objective is observing the construction of the actor Benjamin, especially in his relationship with his father Valdemar, observing not only their actancial and thematic roles, but also the pathemic ones. For that, it will be observed the changes that Benjamin suffers during the narrative, as a pragmatic, cognitive and passional subject, based on the elements of the narrative semiotics and semiotics of passion. As the text, the object of our analysis, is sincretic, we also try to analyze some relation established between the expression and content plans of the text. We referred to the studies of Greimas and Courtés (2012), Bertrand (2003), Greimas and Fontanille (1993), and also to the scholars followers of greimasian semiotics, especially Barros (2002; 2011) and Fiorin (2008). The research made it possible to us to observe the construction of the identity of the actor Benjamin, making us apprehend not only the way of being of the subject, his relation with the spaces where he projects himself, his states of soul, but also the values that the enunciator manipulates in the enunciated text, according to the assumptions of semiotics theory.